The Concept of Insan Kamil in the Thought of Abdul Karim Al-Jilli and its Suitability in the Present Time - Maliberi, Ismam; Qari, Muhammad Farras (Jurnal Riset Agama, 2022)
This study will discuss the concept of insan kamil in al-Jili's thought. The formulation of the problem in this study focuses on how the concept of insan kamil is in al-Jili's view and how the concept fits in the present. This research method uses literature study. The conclusion obtained in this research is that al-Jili conveys the concept Muhammad himself. Al-Jili also in expressing the idea of insan kamil was inspired by Ibn 'Arabi but he criticized several concepts of insan kamil from Ibn 'Arabi. Insan kamil in al-Jili's thinking is relevant today and his position can be an alternative solution to the crisis experienced by modern humans.